Effects of air pollution on ascorbic acid content in the leaves of some woody plants - Otgonbayar, Khishigdelger; Bayarmaa, Jambalsuren; Oyungerel, Shagjjab; Semjid, Tumur (Mongolian Journal of Botany, 2024)
The urban environment poses significant stress and pollution challenges for plants. To assess how plants tolerate these conditions, various physiological and biochemical indicators, including antioxidant compounds like ascorbic acid, are examined. In this study, we investigated the impact of environmental pollution on the ascorbic acid content of plants in such environments.We compared the levels of ascorbic acid in the leaves of 9 species (Larix sibirica Ldb., Padus asiatica Kom., Picea obovata Ldb., Spiraea media F. Schmidt., Armeniaca sibirica Lam., Rosa acicularis Lindl., Salix tenufolia L., Potentilla fruticosa L., Ulmus pumila L.) of woody plants growing in polluted areas along the highway of Ulaanbaatar city and the Shar Khooloin am in Gachuurt area where environment is unpolluted. Minimal changes in ascorbic acid content were observed in L.sibirica and P.obovata species between polluted and unpolluted environments, contrasting with significant variations in U.pumila. Furthermore, the analysis across all 9 woody plant species indicated distinct differences in ascorbic acid content in response to environmental conditions (t (124)=3.5; P<0.001). These results strongly support the notion that environmental pollution impacts ascorbic acid levels in plants. Зарим модлог ургамлын навчны аскорбины хүчлийн агууламжид агаарын бохирдлын үзүүлэх нөлөө Хураангуй. Хот суурин газрын орчин нь ургамлын хувьд орчны бохирдол, стрессийн нөхцөл болдог. Эдгээрийг ургамал хэрхэн тэсвэрлэж байгааг физиологи, биохимийн хэд хэдэн үзүүлэлтээр үнэлдэг ба үүнд антиоксидант олон нэгдлийг ашигладагийн нэг нь аскорбины хүчил юм. Бид тухайн орчинд ургах ургамлын аскорбины хүчлийн агууламжинд орчны бохирдлын үзүүлэх нөлөөллийг тогтоох зорилгоор энэхүү судалгааны ажлыг хийж гүйцэтгэсэн. Үүний тулд Улаанбаатар хотын авто зам дагуух бохирдолтой орчин болон Гачууртын Шар хоолойн ам буюу бохирдолгүй орчинд ургах 9 зүйл (Larix sibirica Ldb., Padus asiatica Kom., Picea obovata Ldb., Spiraea media F. Schmidt., Armeniaca sibirica Lam., Rosa acicularis Lindl., Salix Schwerinii E.Wolf., Potentilla fruticosa L., Ulmus pumila L.) модлог ургамлын навчны аскорбины хүчлийн агууламжийг харьцуулан тодорхойллоо. Бохирдолтой болон бохирдолгүй орчинд ургах ургамлын аскорбины хүчлийн агууламжийн өөрчлөлт L. sibirica, P. obovata зүйлүүдэд бага байсан бол U. pumila-д өөрчлөлт их байхаас гадна судалгаанд хамрагдсан 9 зүйл модлог ургамлын хувьд аскорбины хүчлийн агууламж эдгээр орчинд ялгаатай (p<0.001) байгаа тул орчны бохирдол аскорбины хүчлийн агууламжид нөлөөлж байна гэж үзлээ. Түлхүүр үг: Аскорбины хүчил, навч, агаарын бохирдол